2016
DOI: 10.1186/s40409-016-0063-x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of ultrasonography to the diagnosis of internal bleeding in snakebite envenomation

Abstract: BackgroundIn Africa, snakebite envenomations are frequently complicated by life-threatening hemorrhagic syndromes. The authors of the present study conducted a prospective analysis at the University Hospital of Parakou (north of Benin) for seven months (January 1 to July 31, 2014) to assess the contribution of ultrasonography to the diagnosis of internal bleedings and management of envenomation.MethodsAn ultrasound examination was performed in all patients with clinical envenomation regardless of its severity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…Hemorrhage following trauma represents the leading cause of death in the US population below age 46 and accounts for over 1.5 million deaths per year worldwide . Of these casualties, up to 80% are considered potentially preventable, with the majority stemming from noncompressible bleeding in the torso (NCTH). In particular, closed wounds with internal bleeding are difficult to identify and treat without invasive techniques or advanced imaging modalities, , as their assessment is limited to inferences based on changes in vital signs …”
Section: Introductionmentioning
confidence: 99%
“…Hemorrhage following trauma represents the leading cause of death in the US population below age 46 and accounts for over 1.5 million deaths per year worldwide . Of these casualties, up to 80% are considered potentially preventable, with the majority stemming from noncompressible bleeding in the torso (NCTH). In particular, closed wounds with internal bleeding are difficult to identify and treat without invasive techniques or advanced imaging modalities, , as their assessment is limited to inferences based on changes in vital signs …”
Section: Introductionmentioning
confidence: 99%
“…Although organ hematomas and spontaneous hemoperitoneum are not frequent complications of VICC, they may play a serious role in morbidity and lethality after snakebites in some localities of snake's occurrence (Berling and Isbister, 2015). Tchaou et al (2016) reported in Benin (mostly saw-scaled vipers Echis) internal bleeding in 56% envenomed cases, in this number 22% of hematomas with hemoperitoneum and 12% hemoperitoneum cases. On other hand in Brazil Amazon, systemic bleeding was observed during hospitalization only in 15.3% lanceheads Bothrops snakebite patients with VICC, no hemoperitoneum included (Oliveira et al, 2019).…”
Section: Discussionmentioning
confidence: 80%
“…A thoracoabdominal ultrasound was performed on each patient by a radiologist, looking for internal bleeding [ 14 ] and kidney damage by visualizing the morphological and structural abnormalities of the kidneys. Kidney ultrasounds were performed with a Mode B brand “Mindray ® ” model “DP 8800 Plus” device and associated probe at variable frequencies (2-5MHz).…”
Section: Methodsmentioning
confidence: 99%
“…Viper venoms are responsible for hemorrhagic and necrotizing complications involving many organs, starting with tissue at the bite site. Following envenomation by Echis ocellatus , many hemorrhagic complications have been described: stroke and subarachnoid hemorrhage [ 11 , 12 ], hemothorax [ 13 ], hemoperitoneum [ 14 , 15 ] and kidney injury [ 8 , 16 - 17 ]. Well documented in Asia [ 18 - 21 ] and in South America [ 22 , 23 ], snake venom associated-acute kidney injury (AKI) is poorly explored in SSA and has never been studied in Benin, despite an estimated frequency of 15% of envenomations [ 8 ].…”
Section: Introductionmentioning
confidence: 99%